In Search of Afropeans: A Journey Across Black Europe (KULT_online, 2019)
In his book Afropean: Notes from Black Europe, the photographer, writer, and blogger Johny Pitts sets out in search of Afropeans. His journey takes him as a backpacker through Europe to cities such as Paris, Lisbon, and Stockholm, where he meets people who are African and European at the same time. Pitts’ travelogue contains numerous descriptions of encounters and observations as well as black-and-white photographs showing the everyday life of Afropeans. The author not only makes Afropean identities visible through the interplay of report and visual impressions, but also shows their diversity and dynamics as part of Europe. In addition, he provides impulses for future research with a focus on cross-border and transnational identities that are part of and shape Europe.